2018
DOI: 10.3390/v10080440
|View full text |Cite
|
Sign up to set email alerts
|

The Diverse Roles of microRNAs at the Host–Virus Interface

Abstract: MicroRNAs (miRNAs) are small, non-coding RNAs that regulate gene expression at the post-transcriptional level. Through this activity, they are implicated in almost every cellular process investigated to date. Hence, it is not surprising that miRNAs play diverse roles in regulation of viral infections and antiviral responses. Diverse families of DNA and RNA viruses have been shown to take advantage of cellular miRNAs or produce virally encoded miRNAs that alter host or viral gene expression. MiRNA-mediated chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
112
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(112 citation statements)
references
References 232 publications
(255 reference statements)
0
112
0
Order By: Relevance
“…The sponging effect of circRNAs has been shown to be more efficient than that of the linear miRNA and lncRNA transcripts [29,48]. It has previously been shown that various DNA and RNA viruses (herpesviruses, polyomaviruses, retroviruses, and hepaciviruses) could modulate viral replication via miRNA- mediated gene regulation [49,50]. In contrast, the role of circRNA in viral replication is less well understood.…”
Section: Discussionmentioning
confidence: 99%
“…The sponging effect of circRNAs has been shown to be more efficient than that of the linear miRNA and lncRNA transcripts [29,48]. It has previously been shown that various DNA and RNA viruses (herpesviruses, polyomaviruses, retroviruses, and hepaciviruses) could modulate viral replication via miRNA- mediated gene regulation [49,50]. In contrast, the role of circRNA in viral replication is less well understood.…”
Section: Discussionmentioning
confidence: 99%
“…LMP2A increased survivin by activating the nuclear factor-κB (NF-κB) pathway for resistance from serum deprivation-induced apoptosis in GC cells [13]. At least 44 mature BART miRNAs have been identified [14]. BART miRNAs are expressed at high levels in all EBV-associated carcinomas such as NPC and GC.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs are known to regulate diverse biological pathways including various steps in viral replication [6]. Hence, we studied the role of host miRNAs in regulating viral replication by predicting the host miRNA binding sites among the genome of these viruses.…”
Section: Introductionmentioning
confidence: 99%